Frequency tuning of unimorph cantilever for piezoelectric energy harvesting - Kim, H.-C.; Song, H.-C.; Jeong, D.-Y.; Kim, H.-J.; Yoon, S.-J.; Ju, B.-K. (2007)
Piezoelectric energy harvesting from our surrounding vibration has been studied for driving the wireless sensor node. To change the vibration energy into the electric-energy efficiently, the natural frequency of cantilever needs to be adjusted to that of a vibration source. When adding 6.80g mass on the end of the fabricated cantilever, a natural fi-equency shifts from 136 Hz into 49.5 Hz. In addition, electro-mechanical coupling factor increased from 10.20% to 11.90% and resulted in the 1.18 times increase of maximum output power.